Progressivity of health care financing and incidence of service benefits in Ghana - Akazili, J.; Garshong, B.; Aikins, M.; Gyapong, J.; McIntyre, D. (Oxford University Press in association with The London School of Hygiene and Tropical Medicine, 2012)
The National Health Insurance (NHI) scheme was introduced in Ghana in 2004 as a pro-poor financing strategy aimed at removing financial barriers to health care and protecting all citizens from catastrophic health expenditures, which currently arise due to user fees and other direct payments. A comprehensive assessment of the financing and benefit incidence of health services in Ghana was undertaken. These analyses drew on secondary data from the Ghana Living Standards Survey (2005/2006) and from an additional household survey which collected data in 2008 in six districts covering the three main ecological zones of Ghana. Findings show that Ghana's health care financing system is progressive, driven largely by the progressivity of taxes. The national health insurance levy (which is part of VAT) is mildly progressive while NHI contributions by the informal sector are regressive. The distribution of total benefits from both public and private health services is pro-rich. However, public sector district-level hospital inpatient care is pro-poor and benefits of primary-level health care services are relatively evenly distributed. For Ghana to attain an equitable health system and fully achieve universal coverage, it must ensure that the poor, most of whom are not currently covered by the NHI, are financially protected, and it must address the many access barriers to health care.
Keywords: EMTREE medical terms: article; economics; female; financial management; Ghana; health care delivery; health care financing; human; insurance; legal aspect; male; public health; tax; MeSH: Delivery of Health Care; Female; Financing, Personal; Ghana; Health Services Accessibility; Healthcare Financing; Humans; Male; National Health Programs; Taxes; Universal Coverage